Exploring Flat Faced Longhorn Beetles (Cerambycidae: Lamiinae) from the Reserve Forests of Dooars, West Bengal, India. (17th September 2013) - Saha, Sumana; Özdikmen, Hüseyin; Biswas, Manish Kanti; Raychaudhuri, Dinendra
Abstract : The present study deals with 29 lamiid species under 21 genera of Dooars, West Bengal, India. These include 4 newly recorded species, namely, Macrochenus isabellinus Aurivillius, Aesopida malasiaca Thomson, Pterolophia (Hylobrotus) lateralis Gahan and Nupserha quadrioculata (Thunberg) from India while 16 others (marked by ●) from the state.